Penetrasi Jurnalisme Pasraman di Media Sosial Pada Era Digital - I Ketut Putu Suardana; Rieka Yulita Widaswara (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2021)
The influence of media digitization has led to the development of journalistic media so rapidly. Initially only conventional media experienced disruption to digital. The birth of social media is a concrete form. Besides being used as a medium for uploading thoughts, social media is also used as a publication media such as conventional journalism media. This activity is also carried out by the pasraman. This encourages descriptive qualitative research. Research on the penetration of pasraman journalism that is studied is the activity of pasraman in West Lombok Regency through social media in the digital era. This qualitative research data obtained by the method of observation, interviews and documentation. From the research conducted, it is illustrated that pasraman activities in West Lombok Regency are not very active in social media. A total of 26 (twenty six) pasraman in West Lombok Regency. Only 46.15% use Facebook, 7.69% use Instagram and 7.69% also use Youtube. From December 2020 to February 2021 the most active pasraman on Facebook is Pasraman Yowana Dharma Sastra, on Youtube is Pasraman Widya Giri Malaka, while on Instagram no one has ever uploaded anything.Keywords: Pasraman Journalism, Social Media